Culprit versus non-culprit lesion related adverse cardiac events in patients with obstructive sleep apnoea. Issue 1 (26th July 2013) - Li, Ruogu; Loh, Kelvin; Loo, Germaine; Tai, Bee-Choo; Lee, Chi-Hang
Abstract : Background: In patients with obstructive sleep apnoea (OSA), the relative contribution of culprit versus non-culprit lesions to subsequent major adverse cardiac events (MACE) after acute myocardial infarction (AMI) remains unknown. Elucidating this relationship will shed light on the contributions of OSA to the advancement of coronary artery disease. Methods: In a cohort of 105 patients who underwent an overnight sleep study after AMI, 98 were diagnosed with OSA (Apnoea–Hypopnoea Index (AHI) ≥5). The clinical outcomes at 5-year follow-up were determined. MACE was defined as a composite of cardiac death, reinfarction and repeat revascularisation. A culprit lesion was defined as the lesion involved in the initial AMI, and a non-culprit lesion as any lesion in the entire coronary tree outside the culprit lesion. Results: Eighteen patients (median AHI: 28.1) developed MACE, of whom 12 presented with reinfarction and 6 with repeat revascularisation for stable angina. There was no cardiac death. Based on repeated coronary angiography, the MACE was related to the culprit lesion in 4 patients and the non-culprit lesion in 12 patients. The lesion responsible for the MACE was indeterminate in 2 patients, as coronary angiography was declined. The median duration from index AMI to culprit lesion-related and non-culprit lesion-related MACE were 10.5 and 20 months, respectively. Conclusions: The incidence of MACE among patients with OSA and AMI was 18.4%, and most of the events were related to non-culprit lesions rather than the culprit lesion during the initial AMI.